Pharmacological venous thromboembolism prophylaxis in elective cranial surgery: a systematic review of time of initiation, regimen and duration. (4th May 2022) - Tan, Ian; Pandit, Anand S.; Joshi, Shivani; Khan, Mehdi; Sayar, Zara; Westwood, John-Paul; Cohen, Hannah; Toma, Ahmed K.
Abstract: Introduction: Pharmacological prophylaxis of venous thromboembolism (VTE) requires nuanced decision-making to balance the risk of VTE against haemorrhage. This problem is compounded in neurosurgical patients, in whom postoperative intracranial haemorrhage (ICH) may be catastrophic, compared to non-neuraxial bleeding in other types of surgery. Current major guidelines recommend caution when using pharmacological prophylaxis in elective cranial surgery, but incorporate low-quality evidence and lack precise guidance on timing and duration of anticoagulation. Methods: We aimed to answer the following questions for patients undergoing elective cranial surgery: (1) when is the optimal time to initiate postoperative anticoagulation, and (2) how long should postoperative anticoagulation be continued for? In this systematic review, we screened randomised and non-randomised studies reporting original data on pharmacological VTE prophylaxis in elective cranial surgery. Outcomes of interest were VTE and ICH. Results: Three retrospective, single-centre observational studies met eligibility criteria, with a total of 923 participants. Meta-analysis was not performed due to a high risk of bias across all studies. Through narrative synthesis, we found that patients who developed VTE were significantly more likely to receive their first postoperative dose at a later time (mean: 144 vs. 29 h, p  = .04). Shorter courses of anticoagulation (<7 days) were associated with significantly lower ICH rates ( p  = .03) compared to longer courses (>21 days). Conclusion: The limited evidence favours earlier initiation and shorter courses of thromboprophylactic anticoagulation. These findings are specific to patients undergoing surgery for meningioma or glioma and may not apply to other populations. Randomised controlled trials or robustly designed observational studies are necessary to establish a clearer evidence base.